Potential of Phytoremediation Using Kiambang (Salvinia molesta) for Treating Textile Industry Wastewater in Indonesia - Irhamni; Chalid Mucharrabin; Teuku Muhammad Ashari; Arief Rahman; Husnawati Yahya; Vera Viena; Erdiwansyah (Jurnal Serambi Engineering, 2024)
This study aims to evaluate the effectiveness of phytoremediation using plants in reducing chromium (Cr) levels and modifying pH in batik wastewater. The research was conducted using three experimental tanks: Control Tank (without plants), Tank 1 (with 8 plants) and Tank 2 (with 16 plants). The results showed that in the control tank the pH fluctuated and reached 8.1 on the 9th day, while in tank 1 and tank 2 the pH was more controlled with peak values of 7.9 and 8.2 respectively. The most significant reduction in chromium levels occurred in tank 2, with treatment efficacy reaching 70% on day 9, compared to 45% in tank 1 and 10.5% in the control tank. These results indicate that phytoremediation with more plants can significantly improve the treatment efficiency of batik wastewater, making it a potential and environmentally friendly method for industrial wastewater treatment. The phytoremediation method was carried out by observing variations in the number of plants using 3 reactor tanks. The first tank was a control tank, the second tank (BR2) contained 8 plants and the third tank (BR3) contained 16 plants. Samples were taken on days 3, 6 and 9. The results showed that the highest effectiveness in reducing total chromium (Cr) levels occurred in the third tank (BR3) on day 9, with a reduction of 70%.